Predicted efficacy and tolerance of different dosage regimens of benzylpenicillin in horses based on a pharmacokinetic study with three IM formulations and one IV formulation - Ferran, Aude A.; Roques, Béatrice B.; Chapuis, Laura; Kuroda, Taisuke; Lacroix, Marlène Z.; Toutain, Pierre-Louis; Bousquet-Melou, Alain; Lallemand, Elodie A. (Frontiers in Veterinary Science, 2024)
Benzylpenicillin (BP) is a first-line antibiotic in horses but there are discrepancies between manufacturers and literature recommendations regarding dosing regimen. Objectives of this study were to evaluate pharmacokinetics and local tolerance of four different formulations of BP in adult horses, and to suggest optimized dosing regimen according to the formulation.A cross-over design was used in 3 phases for the intramuscular injection of three different products: procaine BP alone, procaine BP/ benzathine BP combination or penethamate hydriodide were administered IM in the gluteal muscles of 6 horses for 3 days. Single IV administration of sodium BP was performed to the same horses with a dose of 22,000 IU BP/kg bwt 39 weeks after last IM injection. BP plasma concentrations were determined by UPLC assay coupled with mass spectrometry and a PK/PD analysis was conducted to predict the efficacy of various dosing regimens by estimating values of the fT>MIC index for different minimum inhibitory concentrations (MIC). Tolerance at the site of IM injection was monitored by creatine kinase activity quantified with a validated chemistry system and clinical scorings.Except one neurological reaction following one administration of penethamate hydriodide, the tolerance was good. Procaine BP alone, procaine BP/benzathine BP combination or penethamate hydriodide intramuscular administrations at a dosage of 22,000 IU BP/kg bwt q24h for 5 days would yield plasma concentrations that should be effective against bacteria with MIC of ≤0.256, 0.125 or 0.064 mg/L respectively. Of all the tested treatments, the use of a sodium BP by IV Constant Rate Infusion (CRI) for 10 hours a day was deemed to be the most efficient. All the formulations tested in this study are adequate to treat infections with susceptible Streptococcus equi.